(untitled) (Neo Scientific Peer Reviewed Journal, 2026)
This study aims to deeply study the image of Uzbekistan’s fine arts in the international arena in the context of cultural diplomacy in 2017–2025. The main goal of the study is to analyze the strategies of forming a national brand and cultural communication with a global audience. This work uses analytical and comparative methods based on the theory of cultural diplomacy and the concept of "soft power" put forward by Joseph Nye. Exhibitions, biennales, symposia and creative exchange programs in 2017–2025 . The results show that fine arts have served as an important tool in effectively shaping the international image of the state by expressing national values in visual form. At the same time, digital platforms and virtual exhibitions have played an important role in bringing works of art to a global audience. The study analyzed the strategic importance of the integration of art and cultural diplomacy, in combination with economic diplomacy and tourism, in strengthening the national image.